2016
DOI: 10.1002/asia.201600169
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrogen Generation from Formic Acid with Well‐Defined Complexes of Ruthenium and Phosphorus–Nitrogen PN3‐Pincer Ligand

Abstract: An unsymmetrically protonated PN(3) -pincer complex in which ruthenium is coordinated by one nitrogen and two phosphorus atoms was employed for the selective generation of hydrogen from formic acid. Mechanistic studies suggest that the imine arm participates in the formic acid activation/deprotonation step. A long life time of 150 h with a turnover number over 1 million was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
92
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 64 publications
1
92
0
1
Order By: Relevance
“…This could be explained by our recent mechanistic studies of the homogeneous PN 3 P-pincer ruthenium complexes, which showed that the dearomatized complex is the catalytically active species. [10] Accordingly, we treated PPRu with potassium tert-butoxide in DMSO for 24 h, and again applied it to FA dehydrogenation under the same conditions. The reaction proceeded smoothly, producing gases after a short induction period, indicating the catalyst had been successfully activated.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 4 more Smart Citations
“…This could be explained by our recent mechanistic studies of the homogeneous PN 3 P-pincer ruthenium complexes, which showed that the dearomatized complex is the catalytically active species. [10] Accordingly, we treated PPRu with potassium tert-butoxide in DMSO for 24 h, and again applied it to FA dehydrogenation under the same conditions. The reaction proceeded smoothly, producing gases after a short induction period, indicating the catalyst had been successfully activated.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Based on our previous mechanistic studies of t Bu-PN 3 P Ru-catalyzed homogeneous FA dehydrogenation [10] and the reverse reaction (hydrogenation of bicarbonate) using the Rupincer RuP, [12] we proposed a plausible mechanism, as shown in Scheme 2. The mechanism for the Ph-PNpreviously reported to be the catalytically active species.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations